Enhanced water flux through graphitic carbon nitride nanosheets membrane by incorporating polyacrylic acid. Issue 6 (12th January 2018) - Wang, Yanjie; Liu, Lingfei; Xue, Jian; Hou, Jiamin; Ding, Li; Wang, Haihui
Abstract : Membranes assembled from two‐dimensional (2‐D) layered materials have shown potential use in water purification. Recently, a 2‐D graphitic carbon nitride (g‐C3 N4 ) nanosheets membrane exhibits considerable separation performance in water purification. In this study, to further improve this water separation performance, polyacrylic acid (PAA) was introduced to tune the nanochannels formed between the g‐C3 N4 nanosheets. The fabricated g‐C3 N4 ‐PAA hybrid membranes possessed higher water flux without sacrificing much rejection rate compared with that of the g‐C3 N4 membrane; however, noticeable fouling was observed upon addition of the PAA into the membrane composite structure. In addition, the effect of PAA on the morphology, surface hydrophilicity, separation performance, and antifouling properties of the g‐C3 N4 membrane were examined in detail. Overall, incorporating PAA into the g‐C3 N4 nanosheets membrane was an effective and convenient method to improve the water separation performance, which could promote the application of the 2‐D g‐C3 N4 nanosheets membrane in practical ultrafiltration processes. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2181–2188, 2018